1997
DOI: 10.1136/thx.52.5.453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute alterations in inspired oxygen tension on methacholine induced bronchoconstriction in patients with asthma

Abstract: Abstractmild to moderate patients with stable asthma. Background -Recent in vitro and in vivo studies in animals have suggested that am- (Thorax 1997;52:453-457) bient oxygen tension may influence airway Keywords: hyperoxia, hypoxia, bronchoconstriction, responsiveness to bronchoconstrictor methacholine, asthma. stimuli. These observations may have relevance to the management of acute exacerbations of asthma. The present studiesLittle is known about the effect of acute alterwere designed to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The data regarding the effect of hypoxia on airway reactivity are conflicting, as studies report either an increase [145,146], decrease [147] or no change [148,149] in bronchial responsiveness to a methacholine challenge.…”
Section: Chronic Lung Disease At High Altitudementioning
confidence: 99%
“…The data regarding the effect of hypoxia on airway reactivity are conflicting, as studies report either an increase [145,146], decrease [147] or no change [148,149] in bronchial responsiveness to a methacholine challenge.…”
Section: Chronic Lung Disease At High Altitudementioning
confidence: 99%
“…Several studies demonstrate that hypoxia increases bronchial responsiveness to methacholine [116,117], while other studies, using comparable degrees of hypoxic exposure, have shown no change in either the response to methacholine [118,119] or specific airway resistance [120]. In addition to these effects on bronchial hyperresponsiveness, acute isocapnic hypoxia has also been shown to reduce methacholine-induced symptoms of dyspnoea and chest tightness [121], a result which suggests that asthmatic patients may not perceive when they are developing worsening symptoms at high altitude.…”
Section: Hypoxiamentioning
confidence: 99%
“…Both acute and chronic hypoxia alter smooth muscle contractility [13]. In airways, acute hypoxia appears to increase responsiveness both in vitro [4] and in vivo [59]. Surprisingly, the effect of chronic hypoxia on airway smooth muscle is poorly understood, although chronic hypoxia is frequently observed in patients with chronic obstructive pulmonary disease [10] and may play a role in the bronchial hyperresponsiveness associated with this disease [11].…”
mentioning
confidence: 99%